Noni’s root (Morinda citrifolia L.) : A potential natural dyes source for dyeing fabric / Nurul Aini Mohd Lazi - Mohd Lazi, Nurul Aini (Faculty of Applied Sciences, 2009)
This study examines the colour obtained from Noni's root as a potential natural colorant. The dyestuff extracted at different pH condition was applied to the silk fabric. In order to fix the dyes on the silk, different mordant namely alum, copper sulphate, stannous chloride and potassium dichromate was applied followed by dyeing process. The colour shades obtain at different pH with using different mordant on dyed fabric is observed. At lower pH the colour tends to absorb at the shorter wavelength whereas at higher pH the colour tend to shift at the longer wavelength. The range of colours produced by the same dye using different mordants was remarkable, but each mordant had an individually limited range: the used of alum and stannous chloride mordants resulted in a more fading or slightly brighten colour shades on fabric compared with using chrome and copper mordants which darken the colour shades due to the complexation formation. This shows that pH and mordants play an important role of producing various colour shades on dyed fabric using Noni's root pigment.